Biological effects of trans, trans-farnesol in Leishmania amazonensis - Pinheiro, Liliane Sena; Andrade-Neto, Valter Viana; Mantuano-Barradas, Marcio; Pereira, Elisa Cavalcante; Barbosa, Rodrigo Cesar Fernandes; de Oliveira, Marcia Cristina Campos; Menna-Barreto, Rubem Figueiredo Sadok; Cunha-Júnior, Edézio Ferreira; Torres-Santos, Eduardo Caio (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Farnesol, derived from farnesyl pyrophosphate in the sterols biosynthetic pathway, is a molecule with three unsaturations and four possible isomers. Candida albicans predominantly secretes the trans, trans-farnesol (t, t-FOH) isomer, known for its role in regulating the virulence of various fungi species and modulating morphological transition processes. Notably, the evolutionary divergence in sterol biosynthesis between fungi, including Candida albicans, and trypanosomatids resulted in the synthesis of sterols with the ergostane skeleton, distinct from cholesterol. This study aims to assess the impact of exogenously added trans, trans-farnesol on the proliferative ability of Leishmania amazonensis and to identify its presence in the lipid secretome of the parasite. Methods The study involved the addition of exogenous trans, trans-farnesol to evaluate its interference with the proliferation of L. amazonensis promastigotes. Proliferation, cell cycle, DNA fragmentation, and mitochondrial functionality were assessed as indicators of the effects of trans, trans-farnesol. Additionally, lipid secretome analysis was conducted, focusing on the detection of trans, trans-farnesol and related products derived from the precursor, farnesyl pyrophosphate. In silico analysis was employed to identify the sequence for the farnesene synthase gene responsible for producing these isoprenoids in the Leishmania genome. Results Exogenously added trans, trans-farnesol was found to interfere with the proliferation of L. amazonensis promastigotes, inhibiting the cell cycle without causing DNA fragmentation or loss of mitochondrial functionality. Despite the absence of trans, trans-farnesol in the culture supernatant, other products derived from farnesyl pyrophosphate, specifically α-farnesene and β-farnesene, were detected starting on the fourth day of culture, continuing to increase until the tenth day. Furthermore, the identification of the farnesene synthase gene in the Leishmania genome through in silico analysis provided insights into the enzymatic basis of isoprenoid production. Discussion The findings collectively offer the first insights into the mechanism of action of farnesol on L. amazonensis. While trans, trans-farnesol was not detected in the lipid secretome, the presence of α-farnesene and β-farnesene suggests alternative pathways or modifications in the isoprenoid metabolism of the parasite. The inhibitory effects on proliferation and cell cycle without inducing DNA fragmentation or mitochondrial dysfunction raise questions about the specific targets and pathways affected by exogenous trans, trans-farnesol. The identification of the farnesene synthase gene provides a molecular basis for understanding the synthesis of related isoprenoids in Leishmania. Further exploration of these mechanisms may contribute to the development of novel therapeutic strategies against Leishmania infections.